Living with Herds: Human-Animal Coexistence in Mongolia - Fijn, Natasha (Cambridge University Press, 2011)
Domestic animals have lived with humans for thousands of years and remain essential to the everyday lives of people throughout the world. In this book, Natasha Fijn examines the process of animal domestication in a study that blends biological and social anthropology, ethology and ethnography. She examines the social behavior of humans and animals in a contemporary Mongolian herding society. After living with Mongolian herding families, Dr Fijn has observed through firsthand experience both sides of the human-animal relationship. Examining their reciprocal social behavior and communication with one another, she demonstrates how herd animals influence Mongolian herders' lives and how the animals themselves are active partners in the domestication process.